Comparison of Ocular Biometry Profiles in Urban and Rural Cataract Candidates in Eastern China. (15th December 2020) - Liu, Hui; Xu, Zequan; Qian, Zhuyun; Liang, Jianheng; Wei, Kunqiao; Zu, Lipiya; Chen, Xu
Abstract : Purpose . To compare ocular biometric parameters between urban and rural cataract patients in Shanghai, China. Methods . A study of ocular biometry records from urban and rural hospitals was performed for cataract patients at least 50 years of age. The ocular biometrical parameters, which were measured with partial coherence laser interferometry (IOL Master, Zeiss), were axial length (AL), anterior chamber depth (ACD), radius of corneal curvature ( K, including steep/flat/average K ), astigmatism, and axis. Only the right eye record of each patient was analysed. Results . Ocular biometric data included 2839 urban patients (73.15 ± 9.54 years) and 2646 rural patients (73.64 ± 7.32 years). Mean AL, ACD, and K were 24.35 ± 2.34 mm, 3.14 ± 0.58 mm, and 44.38 ± 1.52 D, respectively, in urban patients and 23.58 ± 1.70 mm, 3.08 ± 0.57 mm, and 44.53 ± 1.50 D, respectively, in rural patients. The urban subjects had significantly longer axial lengths (in both univariate and multivariate linear regression analyses) and deeper ACDs (in univariate analysis) than rural subjects p < 0.01 . There was no significant difference in steep K, flat K, and average K between the two groups. With-the-rule (WTR) corneal astigmatism was found in 1787 eyes (32.58%), against-the-rule (ATR) corneal astigmatism was found in 2727 eyes (49.72%), and oblique corneal astigmatism was found in 971 eyes (17.70%). Conclusions . We report biometry and astigmatism data in a large cohort of urban and rural adult subjects for the first time. In our study, a short AL, shallow ACD, and axis turned in an ATR direction had higher prevalence rates in the rural subjects. This profile of ocular biometric data and corneal astigmatism will be helpful in planning for intraocular lens (IOL) power calculations and astigmatism correction in subjects in different locations.